Optimally Sharp Energy Filtering of Quantum Particles via Homogeneous Planar Inclusions - Valagiannopoulos, Constantinos (Scientific reports, 2020)
Some of the most influential players from academia and industry have recently expressed concrete interest for quantum engineering applications, especially for new concepts in controlling and processing the quantum signals traveling into condensed matter. An important operation when manipulating particle beams behaving as matter waves concerns filtering with respect to their own energy; such an objective can be well-served by a single planar inclusion of specific size and texture embedded into suitable background. A large number of inclusion/host combinations from realistic materials are tried and the optimally sharp resonance regimes, which correspond to performance limits for such a simplistic structure, are carefully identified. These results may inspire efforts towards the generalization of the adopted approach and the translation of sophisticated inverse design techniques, already successfully implemented for nanophotonic setups, into quantum arena.